103k views
1 vote
If -7.6(x - 1) = 7.3 - 7.4x, find the value of -2x.

2 Answers

3 votes

Answer:

3

Explanation:

-7.6x+7.6=7.3-7.4x

-7.6x+7.4x=7.3-7.6

-0.2x=-0.3

X=-0.3/-0.2

X=3/2

2x. means multiply the ans you get for x by 2

2(3/2)

=3

User Duckmike
by
4.5k points
2 votes

Answer:

-3

Explanation:

Step 1: Write equation

-7.6(x - 1) = 7.3 - 7.4x

Step 2: Solve for x

Distribute -7.6: -7.6x + 7.6 = 7.3 - 7.4x

Add 7.6x on both sides: 7.6 = 7.3 + 0.2x

Subtract 7.3 on both sides: 0.3 = 0.2x

Divide both sides by 0.2: x = 1.5

Step 3: Find -2x

-2(1.5) = -3

User RoundPi
by
5.2k points